MODEL TESTING WITH WOOD MATERIALS IN INDOOR AND OUTDOOR USE - Veronica, Selly; Hasibuan, Ahmad F.A.H; Luke, Evania F; Thoha, Gweneth J.A; Kurniawan, Muhammad R; Alparizi, Rapli I (Border: Jurnal Arsitektur, 2024)
Wood is a natural material that is easy to find and can be used for building materials. A large number of types of wood causes errors in the selection of wood based on its use. This study aims to determine the reactions and changes that occur in the wood used in the model. This study used an experimental method carried out on wooden models through two indoor and outdoor placements. Indoor testing was carried out by placing the model in a closed room with an average room temperature of 24-33°C for 14 days, while outdoor testing was carried out by placing the model in an open space for 7 days. From the results of the analysis carried out, wood materials can be used indoors and outdoors. However, several factors related to wood’s type, nature, and quality must be considered. Some types of wood require special care such as coating the wood so that it can be used optimally outdoors.From these experiments, it can be concluded that wood has several types, and we must know the characteristics of wood according to its use.